Peran Komite Madrasah sebagai Advisory Agency Kebijakan Mutu Akademik di Madrsah Berprestasi Nasional Madrasah Tsanawiyah Negeri 2 Kota Kediri - Nurul Ahsin; Mu'awanah (Pascasarjana IAIN Sultan Amai Gorontalo, 2021)
Madrasah Tsanawiyah Negeri (State Islamic Junior High School) 2 Kediri City is a national achieving madrasa that has won various achievements at national and international levels in academics, research by Scientific Youth, and institutions. National achievements were also achieved with the achievement of awards in the field of inspirational madrasah leadership, and madrasas with national integrity. In this study, a qualitative approach was used during the research process with a case study design. Participant observation and in-depth interviews and documentation studies were applied during data collection. This study shows that the achievement of the academic and non-academic quality of this madrasah cannot be separated from the role of the madrasah committee in providing considerations during the planning, implementation, and monitoring process of the quality of Madrasah Tsanawiyah Negeri 2 Kediri. The synergistic cooperation between the government, the madrasa academic community, and the madrasa committee resulted in the achievement of the quality of the madrasa at a national level.